2023
DOI: 10.5114/hpc.2023.128805
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sports on Emotional Control in Cadets of the National Guard Оf Ukraine at the Beginning of the War

Ivanna Bodnar,
Andriі Andres,
Valeriy Kryzhanovskyi
et al.

Abstract: Background. The ability to adequately respond to various emotional situations is vital for law enforcement officers to work effectively in peacetime. In times of war, the importance of emotional control increases. Material and methods. A survey (in Google forms) of cadets of the Kyiv Institute of the National Guard of Ukraine (n=282) was conducted. Depending on whether they played sports, the respondents were divided into 2 groups (n=171 and n=111, respectively). Spielberger's method was advocated. And the Cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…As a result of a series of conducted studies, we identified professionally important qualities and factors that determine the formation of psychophysical readiness of the personnel of the National Guard of Ukraine for effective military-professional activities [1,[15][16][17]. The factors that we consider to determine the formation of psychophysical readiness of the personnel of the National Guard of Ukraine include: 1) cognitive qualities: attention (persistence, concentration, switching ability, distribution, and volume), thinking (strategic and logical); leadership qualities: the ability to manage personnel and achieve common goals; 2) courage (fearlessness, confidence in one's abilities, perseverance) and emotional intelligence (ability to understand others' feelings and influence them, ability to work in a group); 3) physical qualities (agility: ability to maintain dynamic balance, ability to differentiate movements in space, sense of rhythm), strength: maximum strength, speed strength.…”
Section: Preliminary Stage Of the Researchmentioning
confidence: 99%
“…As a result of a series of conducted studies, we identified professionally important qualities and factors that determine the formation of psychophysical readiness of the personnel of the National Guard of Ukraine for effective military-professional activities [1,[15][16][17]. The factors that we consider to determine the formation of psychophysical readiness of the personnel of the National Guard of Ukraine include: 1) cognitive qualities: attention (persistence, concentration, switching ability, distribution, and volume), thinking (strategic and logical); leadership qualities: the ability to manage personnel and achieve common goals; 2) courage (fearlessness, confidence in one's abilities, perseverance) and emotional intelligence (ability to understand others' feelings and influence them, ability to work in a group); 3) physical qualities (agility: ability to maintain dynamic balance, ability to differentiate movements in space, sense of rhythm), strength: maximum strength, speed strength.…”
Section: Preliminary Stage Of the Researchmentioning
confidence: 99%
“…Available data in the specialized literature indicate that military personnel, cadets, and participants in combat often experience negative emotions [9][10][11] during peacetime or in the rehabilitation phase. However, there are not many scientific studies dedicated to highlighting Andrii Andres et al The impact of sports activities on the psycho-emotional state of cadets in higher education institutions during wartime the emotions experienced by military personnel in wartime conditions [12]. In stressful situations, the interaction of these indicators has not been studied.…”
Section: Introductionmentioning
confidence: 99%